Developing an Oral Hygiene Education Song for Children and Teenagers in Nigeria - Olushola Ibiyemi; Folake Lawal; Mary Osuh; Tolu Owoaje; Ejiro Idiga; Omotayo Fagbule; Olabode Ijarogbe (Elsevier, 2022)
ABSTRACT: Background: Oral diseases mainly caused by poor oral hygiene are a major public health problem affecting over half of the world's population. Oral hygiene education targeted at children and teenagers in schools is an important approach in addressing this problem. Folk songs in the language and cultural context children and teenagers are familiar with appears to be a promising tool and alternative to traditional oral hygiene education. Objectives: This paper aims to report how a local traditional song on oral hygiene education amongst children and teenagers in southwestern Nigeria was developed with a view to providing information on how the song can be developed in other languages as well as how other oral health education songs can be developed. Method: Oral health professionals from the University College Hospital, Ibadan, and music experts from the University of Ibadan, in collaboration with traditional/local musicians, parents/guardians, schoolteachers, and community heads, took part in the development of the song over a period of 6 months. Developing the tool involved certain processes which were validated and evaluated. These processes included developing the lyrics, choosing the type of song, creating the melody, and producing and finishing the song as an oral hygiene education tool. Written and audio documentations of the processes were done. Results: A 90-second oral hygiene education song was developed in English and later translated into Yoruba. The numerous steps, collaborations, and meetings required in the development of the song were associated with many learning opportunities including team-building, understanding cultural contexts, effective collaboration, leadership, and communication skills. Conclusions: Creating new and effective oral hygiene education tool requires various processes and multiple steps and resources. However, it is a necessary and worthy exercise in ensuring sustainable and adequate oral hygiene, especially amongst children and teenagers in underserved populations, as we move into the future.